Analisis Peran Pemerintah Desa Dalam Mewujudkan Pembangunan Desa Mandiri (Studi Kasus Desa Kalanganyar Kecamatan Karanggeneng Kabupaten Lamongan) - Prasasti, Putri Fiorina; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Independent village is a village development concept regulated in Law Number 6 of 2014 concerning Villages, which gives authority to the village government to build based on local potential and wisdom. This study aims to analyze the role of the Kalanganyar Village Government in realizing independent village development. The theory used in this study is the role theory according to Gede Diva (2009) which includes the role as a regulator, facilitator, and catalyst, as well as aspects of village development according to Hakim and Wibowo (2024) which include community empowerment, economic independence, management of natural resources, education and health, infrastructure and technology, and sustainability. The research method used is descriptive with a qualitative approach. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the Kalanganyar Village Government has carried out its role optimally. As a regulator, the village government sets local policies based on culture and community agreements. As a facilitator, the government provides participatory space and supports training and development of village facilities. As a catalyst, the government collaborates with external institutions such as universities, related agencies, and CSR to support development programs. Although there are still obstacles, the Kalanganyar Village Government is able to resolve them collaboratively and gradually in order to realize village independence.